Paramagnetic (1,3-diborolyl)ruthenium triple-decker complexes and transformation into diamagnetic complexes having bridging 1,3-diborafulvene ligands - Mutseneck, Elena V.; Wadepohl, Hubert; Enders, Markus; Kudinov, Alexander R.; Siebert, Walter (European journal of inorganic chemistry, 2010)
The paramagnetic triple-decker complexes [(Cp*Ru)2μ-(CMe)3(BCl)(BMe)] (3b) and [(Cp*Ru)2μ-(CMe)3(BCl)2] (3c) are formed by refluxing a mixture of [Cp*RuCl]4 and pentamethyl-2,3-dihydro-1,3-diborole in thf. In CH2Cl2 under air complex 3b slowly looses a hydrogen atom with formation of the diamagnetic triple-decker [(Cp*Ru)2μ-η5:η6-(CMe)3(BCl)(BCH2)] (4b) with the unsymmetrical dihydrodiborafulvene derivative in a bridging position. The analogous complex [(Cp*Ru)2μ-η5:η6-(CMe)3(BMe)-(BCH2)] (4a) is obtained by interaction of HCl with the triple-decker [(Cp*Ru)2μ-(CMe)3(BMe)2] (3a). According to calculations, complexes 4a and 4b have an almost non-distorted triple-decker arrangement with a strong bending of the B=CH2 group toward one of the Ru atoms. For the formation of 3b and 3c the chloro-containing sandwich complexes [Cp*Ruη5-(CMe)3(BCl)(BR1)] (2b,c; R1 = Me, Cl) are proposed as intermediates. The constitutions of the complexes are derived from NMR, MS and DFT data, and the molecular structure of 3b is confirmed by an X-ray diffraction analysis.
First published: 23 June 2010
Gesehen am 29.11.2022